2018
DOI: 10.1155/2018/2874012
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Regression of Hydroxycarbamide Induced Actinic Keratoses after Switching to Anagrelide

Abstract: Hydroxycarbamide (HC) is the first-line treatment for certain myeloproliferative neoplasms, such as polycythemia vera and essential thrombocytosis (ET). In a subset of these patients long-term treatment with HC can result in the development of confluent actinic keratoses (AK) followed by invasive keratinocytic carcinomas (“squamous dysplasia”), preferentially on sun-exposed skin. Discontinuation or dose reduction of HC may result in partial improvement. A 59-year-old farmer after 14 years on HC (2 gr/d) and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…By interfering with DNA synthesis, HC has the potential to be mutagenic and therefore provides a plausible biological mechanism for skin cancer development. By acting synergistically with ultraviolet light, HC can increase the risk of development of other non‐cancerous skin changes such as actinic keratoses (AK) [11], with case studies highlighting sustained regression of AKs after discontinuation of HC [12]. However, in our study older age, male gender, type of MPN and previous history of skin cancer were the only statistically significant prognostic risk factors for skin cancer development.…”
Section: Discussionmentioning
confidence: 57%
“…By interfering with DNA synthesis, HC has the potential to be mutagenic and therefore provides a plausible biological mechanism for skin cancer development. By acting synergistically with ultraviolet light, HC can increase the risk of development of other non‐cancerous skin changes such as actinic keratoses (AK) [11], with case studies highlighting sustained regression of AKs after discontinuation of HC [12]. However, in our study older age, male gender, type of MPN and previous history of skin cancer were the only statistically significant prognostic risk factors for skin cancer development.…”
Section: Discussionmentioning
confidence: 57%
“…52 Indeed, 1 has been used to successfully resolve a case of confluent actinic keratoses, a skin lesion that can progress to invasive squamous cell carcinoma. 80 As a result of the observations with velcrins, clinical applications are being explored in the context of BAY 2666605 (39), which has entered into trials in patients with metastatic melanoma and other advanced solid tumors where the downregulation of induced myeloid leukemia cell differentiation protein (Mcl-1) will be monitored as a biomarker. 81 Preclinical studies with 39 have demonstrated antitumor effects in patient-derived xenograft models of ovarian cancer and sarcoma, and since the molecule is CNS penetrant, it has been shown to have the potential to treat glioblastomas.…”
mentioning
confidence: 99%
“…These data suggested that as a potential therapeutic approach, the broader cytotoxic effects of molecules with a profile similar to 20 in normal tissues would be limited . Indeed, 1 has been used to successfully resolve a case of confluent actinic keratoses, a skin lesion that can progress to invasive squamous cell carcinoma . As a result of the observations with velcrins, clinical applications are being explored in the context of BAY 2666605 ( 39 ), which has entered into trials in patients with metastatic melanoma and other advanced solid tumors where the downregulation of induced myeloid leukemia cell differentiation protein (Mcl-1) will be monitored as a biomarker .…”
mentioning
confidence: 99%